Evaluating antimicrobial efficacy of new commercially available silver dressings - Cavanagh, Marion H (Int Wound J, 2010)
Prevention and treatment of bacterial colonised/infected wounds are critical. Many commercially available silver dressings claim broad‐spectrum bactericidal activity over days and are indicated for serious conditions including burns and ulcers. However, there is no peer‐reviewed literature available for many newer dressings. This study compared the activity of some of these dressings. Six silver‐containing dressings were compared using log reduction, silver release and corrected zone of inhibition assays. Only the nanocrystalline silver dressing was bactericidal against Staphylococcus aureus, and the only other dressing that produced any log reduction was a silver collagen matrix dressing. These two dressings and a silver alginate dressing produced zones of inhibition, although the collagen matrix and alginate dressings had decreasing zone sizes over time, and the latter liquefied after five transfers. The remaining dressings (two ionic silver foam dressings and a silver sulphate dressing) did not produce zones of inhibition. For the foam, alginate and collagen matrix dressings, antimicrobial activity was related to silver release. The silver sulphate dressing released large quantities of silver, but only through the dressing edges, as the wound‐contacting surface appeared to be hydrophobic. The results of this study emphasise the importance of confirming product claims regarding silver dressing efficacy.